Declining Pre-bloom Calanus finmarchicus Egg Production Adjacent to Two Major Overwintering Regions in the Northeastern Atlantic - Jacobsen, Sólvá; Gaard, Eilif; Hátún, Hjálmar (Frontiers in Marine Science, 2022)
Calanus finmarchicus is a key secondary producer in the North Atlantic. Shortly prior to the spring bloom the animals ascend from diapause at depth to surface waters, where the females spawn partly, based on winter lipid reserves. C. finmarchicus eggs are an important prey of first feeding fish larvae inhabiting North Atlantic shelves during early spring and are thus essential for larval survival. Comprehensive late April surveys have been carried out on and around the Faroe shelf, which is located between the Northeast Atlantic and the Nordic Seas, for more than two decades. One aim is to investigate the critical match-mismatch between the spring bloom development, zooplankton reproduction and occurrence of first feeding fish larvae. In this study, we examine spatial and temporal changes in pre-bloom reproductive activity of C. finmarchicus on and around the shelf using a unique dataset of more than 8,000 examined females sampled during the period 1997–2020. Enhanced productivity was observed on the north-western side of the shelf, where the main flow of oceanic water to the inner permanently well mixed shelf takes place. We attribute this increased productivity to enhanced food (phytoplankton) availability in the seasonally stratified outer shelf, slightly upstream of the main egg production area. Both individual egg production rates and the fraction of spawning females declined throughout the Faroe shelf during the examined period. This decline could not be explained by the employed environmental parameters. The declining pre-bloom egg production may have consequences for first feeding fish larvae.